Prosthodontic service as an index to preventive dentistry - Silva, Pilar; Boncan, Ricardo; Ladao Jr., Joaquin (Adviser).
It seems like whenever a preventive dental health program fails to be instituted to adequate level, therapeutic, restorative or mechanical forms of rehabilitation, for those who are afflicted by caries or periodontal disease with consequent partial or complete loss of teeth, seems to be the only way to bring back function. One therapeutic means is prosthodontic service which alleviates the condition edentulous people have to undergo, Foremost of these are the function of mastication and the improvement of facial appearance. Prosthodontic service or rehabilitation can reflect the success or failure of the government preventive dental health program. This paper will try to study the most frequent type of prosthodontic service asked for in the U.P. College of Dentistry within a five year period (1984 - 1989) and from this we will try to see if this reflects the status of the preventive dentistry program of the country. As we all know, any success in the preventive dentistry program will show a decrease in the number of edentulous people within the population.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Prosthodontics; Preventive dentistry